Konsep Al-Ibtila’ Menurut Islam: Tinjauan Deskriptif Berdasarkan Beberapa Ayat Al-Quran dan Al-Hadith: The Concept of Al-Ibtila' According to Islam: A Descriptive Review Based on Several Verses of the Quran and Al-Hadith - Syed Abdul Rahman, Syed Mohammad Hilmi; Mohammed Dawam, Rohaida; Mohd Azhar, Muhammad Hazim (Al-Basirah Journal, 2021)
Al-Ibtila ’is one of the topic of discussion in the al-Qada’ al-Qadar debate. It is a concept of test that happened to human beings while exploring their life. It must be understood to make sure that human are prepared to whatever the challenges or test come to their way. Using a descriptive method that focused to the concept of al-Ibtila ’as the main topic of discussion, this paper has presented the understanding of the test reality based on the concept of al-Ibtila’ according to Islam. The construction of this understanding is based on the language definition and terminology as well as some selected verses of the Qur'an and Hadith. Ultimately, the fact of al-Ibtila ’is the sunnah of life and the world is a testing state. Every human being will certainly face a test and it is given in various forms including their pleasure, suitability and hardship. In short, the understanding of al-Ibtila 'will increase the perceptiveness of faith in al-Qada' al-Qadar.